Pyrimidine derivatives as novel acidizing corrosion inhibitors for N80 steel useful for petroleum industry: A combined experimental and theoretical approach - Haque J.; Ansari K.R.; Srivastava V.; Quraishi M.A.; Obot I.B. (My University, 2025)
The corrosion inhibition performance of two pyrimidine derivatives namely 5-styryl-2,7-dithioxo-2,3,5,6,7,8-hexahydropyrimido[4,5-d] pyrimidin-4(1H) one (PP-1) and 5-(2-hydroxyphenyl)-2,7-dithioxo-2,3,5,6,7,8-hexahydropyrimido[4,5-d]-pyrimidin-4(1H) one (PP-2) on N80 steel corrosion in 15% HCl has been studied using gravimetric method, electrochemical impedance spectroscopy (EIS), potentiodynamic polarization, atomic force microscopy (AFM), scanning electron microscopy (SEM), DFT, molecular electrostatic potential and Monte Carlo simulation. The corrosion inhibition efficiencies at optimum concentration (250 mg/L) are 89.1% (PP-1) and 73.1% (PP-2) respectively at 308 K. The corrosion inhibition efficiency increases with increase in concentration and decreases with temperature. PPs obeyed Langmuir adsorption isotherm. AFM and SEM analyses supported formation of protective film on N80 steel in presence of inhibitors. DFT and Monte Carlo simulation calculations supported experimental results. © 2017 The Korean Society of Industrial and Engineering Chemistry